Impact of agricultural practice on the Sr isotopic composition of food products: Application to discriminate the geographic origin of olives and olive oil. (July 2017) - Techer, Isabelle; Medini, Salim; Janin, Myriam; Arregui, Maider
Abstract: The Sr isotopic compositions ( 87 Sr/ 86 Sr) of varied organs (branches, leaves and olives) of olives trees (Olea europaea) and those of their growing environment (soils, waters, agricultural products) were determined in two distinct agricultural contexts to discuss the origin of Sr as a function of the irrigation and fertilization techniques. The two studied sites belong to the same geographic area and the same geological basement and soils, but were by subjected to different agricultural practices in terms of irrigation and supply of fertilizers and protection products. The conventional and biological agriculture modalities were defined and tested. Homogeneous 87 Sr/ 86 Sr ratios were measured in the various organs of the trees from a given site. However, the composition was significantly different at the two studied sites. When considering a biological agricultural modality, significant correlations are obtained between the Sr isotopic composition of the tree organs, the soils and the irrigation waters. The mobile and exchangeable fractions of the soils have identical 87 Sr/ 86 Sr ratios that were transferred to the trees. In case of a conventional agriculture with more intensive irrigation and spreading of plant-protection products, a clear impact of these products is visible in the soils. The 87 Sr/ 86 Sr ratio of the olive trees not only derives from soil sources, but also from added products with a clear role of the irrigation. A slight but noticeable foliar uptake of anthropogenic Sr is also observed. The disturbance of the soil and tree Sr isotope composition as a function of the agricultural practices is discussed in the context of using the Sr isotopic tool as a tracer of the geographic origin of olives and olive oil. Highlights: The origin of Sr in trees in agricultural contexts is discussed. Irrigation and fertilization have significant effect on trees Sr isotope ratio. Sr isotope could be used as tracer of the geographic origin of agri-food products. The efficiency of the tracing tool is strictly dependent on agricultural modalities.